Rules Without...: Some Critical Reflections on the Federal Corporate Sentencing Guidelines - Jeffrey S. Parker (Washington University Law Quarterly, 1993)
Essentially, what is wrong with the Guidelines is that they are rules "without"-without rationality, without authority, without constitutionality. What went wrong is an old pattern of deficiency in government that seems to recur in endless variation: power without adequate discipline becomes tyranny. The possible solutions are equally simple: reinforce the discipline, or withdraw the power. The former tends to be a risky strategy for a free people, for most disciplinary procedures can be circumvented. Therefore, perhaps it is time to reexamine whether the power should be granted at all, that is, whether the Sentencing Commission should be put out of the business of corporate sentencing.
Keywords: Criminal liability of juristic persons; Sentencing guidelines (Criminal procedure)